An Evaluation of the coursebook “English for Information Technology I” for second–year students of University of Information and Communication Technology under Thai Nguyen University= Đánh giá giáo trình Tiếng Anh chuyên ngành Công nghệ thông tin I " dùn - Trần, Minh Thành (ĐHNN, 2017)
41 p. + CD-ROM